Supplementation with Resveratrol, Piperine and Alpha-Tocopherol Decreases Chronic Inflammation in a Cluster of Older Adults with Metabolic Syndrome - Pastor, Raul Francisco (2020)
Metabolic Syndrome (MetS) is increasing worldwide regardless of culture, genetic, gender, and geographic differences. While multiple individual risk factors, such as obesity, hypertension, diabetes, and hyperlipidemia, can cause cardiovascular disease (CVD), it is the intercurrence of these risk factors that defines MetS as a cluster that creates an environment for atherosclerosis and other manifestations of CVD. Despite the advances in the knowledge and management of each of the components of MetS, there are two molecular biology processes, chronic inflammation and oxidative stress, which are still underdiagnosed and undertreated. In order to assess the effect of a dietary supplement on chronic inflammation in MetS, we conducted a clinical trial with volunteers receiving a formula composed of resveratrol, piperine and alpha tocopherol (FRAMINTROL®), together with their habitual treatment, for three months. The inflammatory state was evaluated by ultrasensitive C reactive protein (US CRP) and ferritin in plasma, and oxygen consumption and chemiluminescence in neutrophils. The results showed that ferritin decreased by 10% (p < 0.05), US-CRP by 33% (p < 0.0001), oxygen consumption by 55% (p < 0.0001), and spontaneous chemiluminiscence was by 25% (p < 0.005) after treatment. As far as we know, this is the first study showing a chronic inflammation decrease in MetS patients due to the administration of a biopower Resveratrol-piperine and alpha tocopherol dietary supplement together with conventional therapy.